Bifunctional WOx/SiO2 catalysts for hydrogen-free upgrading of B100 and bio-ethylene to SAF and green diesel precursors via olefin metathesis and deoxygenation - Mochamad Solehudin; Kanokwan Wengwirat; Pratya Promchana; Yingyot Poo-arporn; Wanwisa Limphirat; Kittisak Choojun; Tawan Sooknoi (Fuel, 2026)
• Hydrogen-free upgrading of palm biodiesel (B100) with bio-ethylene at 1 atm. • Bifunctional WO x /SiO 2 catalyzes olefin metathesis and deoxygenation to fuel precursors. • Methyl oleate yields SAF-range C 9 –C 14 olefin precursors via cross-metathesis with ethylene. • Methyl palmitate forms GD-range C 15 –C 18 precursors via ketene and decarbonylation routes. • 5 wt% WO x /SiO 2 delivers optimal activity and selectivity with high carbon efficiency. This work presents a hydrogen-free catalytic route for upgrading palm-derived biodiesel (B100) into olefinic precursors for sustainable aviation fuel (SAF) and green diesel (GD) using bifunctional WO x /SiO 2 catalysts under atmospheric pressure. The catalysts integrate olefin cross-metathesis, mediated by surface W CH 2 species, with deoxygenation via Lewis-acidic W O sites, enabling selective C C bond exchange and C O bond cleavage without external hydrogen or noble metals. Detailed mechanistic studies revealed that methyl oleate (MO) rapidly undergoes cross-metathesis with ethylene to yield SAF-range C 9 –C 14 precursors, while methyl palmitate (MP) contributes primarily to GD (C 15 –C 18 ) through ketene intermediates and decarbonylation–hydrogen transfer pathways. Contact time and temperature experiments confirmed that MO conversion is kinetically favored at milder conditions, whereas MP-derived pathways dominate at higher temperatures and extended residence times. Catalyst loading studies show that the 3 and 5 wt% WO x /SiO 2 catalysts are dominated by highly dispersed isolated and polymeric WO x species, which exhibit higher accessible acidity and consequently promote secondary cracking reactions. In contrast, the 8 wt% WO x /SiO 2 catalyst contains a higher fraction of bulk crystalline WO 3 domains, resulting in reduced surface acidity and suppressed cracking. Overall, 8 wt% WO x /SiO 2 delivers reasonable rates with high selectivity toward SAF/GD precursors, while minimizing secondary cracking. It can be regenerated and recycled with substantial recovery of catalytic performance, establishing a robust, low-pressure, and hydrogen-free pathway for scalable renewable fuel production from B100.
Keywords: Catalysis for Biomass Conversion; Catalysis and Hydrodesulfurization Studies; Porphyrin Metabolism and Disorders